2004
DOI: 10.1063/1.1702136
|View full text |Cite
|
Sign up to set email alerts
|

Fast energy transfer in layer-by-layer assembled CdTe nanocrystal bilayers

Abstract: We report on efficient resonant energy transfer in bilayers of water-soluble CdTe quantum dots. The bilayers of CdTe nanocrystals of two different sizes capped by short-chain thiols were formed by layer-by-layer assembly. Temporally and spectrally resolved fluorescence spectroscopy reveals spectral diffusion of the fluorescence signal for quantum dots within one layer as well as rapid (254 ps) energy transfer from layers of small dots to layers of larger dots, which is fast for nanocrystal pairs. Subspecies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 20 publications
5
127
0
Order By: Relevance
“…54 The length of the ligand is only taken into account once, as the ligand shells can interpenetrate. 19,54 This minimum separation of 2.7-3.2 nm for QD1, QD2, and QD3 will only be achieved at the highest concentrations and is still a relatively large separation in context of Dexter energy transfer. In contrast the Förster mechanism is less sensitive to the donoracceptor separation than the Dexter mechanism and can occur over longer separation distances.…”
Section: Theoretical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…54 The length of the ligand is only taken into account once, as the ligand shells can interpenetrate. 19,54 This minimum separation of 2.7-3.2 nm for QD1, QD2, and QD3 will only be achieved at the highest concentrations and is still a relatively large separation in context of Dexter energy transfer. In contrast the Förster mechanism is less sensitive to the donoracceptor separation than the Dexter mechanism and can occur over longer separation distances.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…15 Numerous reports have been published on energy transfer in QD structures formed using these techniques among others. [16][17][18][19][20][21][22][23] To date there have been only a few reports investigating the influence of the QD concentration on the optical properties and/or energy transfer in monodispersed QD layers, 16 even though they are the fundamental building blocks of many of the systems and devices highlighted above. It is important to consider the QD concentration when comparing the results reported in different publications; its impact on the signal levels, outcome of measurements and performance of devices has to be determined and taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the number of separation layers can control the distance between active layers, LbL film is a perfect architecture to study FRET applications. 35 Layer-by-layer deposition of inorganic materials in biological systems is common. Lustrin is a protein with polycationic domains, managing formation of layer-by-layer assembly of aragonite in mollusk shell, 36,37 and similarly silicatein protein is responsible for the formation and assembly of complex silica structures in a diatom, Cylindrotheca fusiformis.…”
Section: à25mentioning
confidence: 99%
“…12 In thin film devices, different structures and types of NCs have been investigated to improve the energy transfer by using layerby-layer ͑LbL͒ assembly technique, which allows for the sequential arrangement of multilayered micro-to nanoscale structures of NCs. [13][14][15] Franzl et al 16 demonstrated efficient FRET in LbL assembled bilayers of CdTe NCs. In another structure, alternating layers of NCs and polyelectrolytes have been assembled to form a funnel-like bandgap variation toward the center NC layer for efficient energy harvesting.…”
mentioning
confidence: 99%